ANALYSIS OF THE RESULTS OF FIVE YEAR PATIENTS FOLLOW-UP IN PAROXYSMAL ATRIAL FIBRILLATION TREATED WITH ANTIARRHYTHMICS - T. A. Rybakova; V. V. Stolyarova; M. G. Nazarkina; N. Yu. Leschankina (Российский кардиологический журнал)
Aim. To analyze the results of 5-year follow-up of the paroxysmal atrial fibrillation patients (PAF) taking antiarrhythmic therapy (AAT)Material and methods. Patients (n=500) were selected to 11 groups: I — healthy, II — controls, III-XI — PAF taking AAT. The baseline parameters of heart rate variability (HRV) were assessed during 5-year follow-up.Results. Decrease of SDNN does 1,9 times increase the risk of AF development during the first 3 months from preventive AAT start. Decrease of RMSSD does 3,9 times increase the risk of AF during the first 2 weeks, and 1,9 times — 3 months; decrease of Delta X increases the risk of AF 3,9 times during 2 weeks, 2 times — during 3 months, 1,4 times — during 6 months, 1,3 times — during 12 months and 3 years. Increase of Amo does 1,8 times increase the risk of AF during first 3 months. If there was baseline decrease of Delta X and RMSSD, then within 2 weeks the AF paroxysm developed in 7,9% patients, and in 3 months — 15,9% patients. With the decrease of Delta X and RMSSD, in combination with low SDNN, the probability of sinus rhythm retention during 1 year is 51,2%.Conclusion. PAF patients taking preventive AAT demand for ECG assessment of HRV parameters no less than once per 3 months.